Health-and-Environment Indicators in the Context of Sustainable Development - von Schirnding, Yasmin E. (Can J Public Health, 2002)
This paper gives a broad overview of issues relevant to the development and use of health-and-environment indicators in the broader context of sustainable development. Criteria for the construction of indicators are given, and their key characteristics are highlighted. Selected international indicator initiatives are discussed, as well as the concept and use of core indicators in policy and planning. Finally, an organizational framework for the consideration of health-environment-development linkages is presented, which can be used in the development of health-and-environment indicators in various contexts. This framework is the Driving forces-Pressures-State-Exposures-Health Effects-Actions framework (DPSEEA) of the World Health Organization (WHO). It is a descriptive representation of the way in which various driving forces generate pressures which affect the state of the environment, and ultimately human health through the various exposure pathways by which people come into contact with the environment. Throughout the paper, emphasis is placed on work done within the UN system, in particular that of the WHO, and examples of suites of indicators developed and in use are provided.